Abrasive Free Chemical Mechanical Planarization of Semi-Polar (11–22) GaN: Effect on Structural and Surface Properties and Subsequent Homoepitaxial Growth. (20th March 2018) - Parthiban, P.; Rahman, A. Azizur; Bhattacharya, Arnab; Das, D.
Abstract : The implementation of abrasive free chemical mechanical planarization (AFCMP) as an intermediate step to improve the structural and surface qualities of semi-polar (11–22) GaN device layer has been investigated. As-grown semi-polar (11–22) GaN surfaces were polished and characterized for surface finish using AFM and optical surface profiler to investigate the effect of surface planarity. Atomically flat surface with rms roughness of 4 Å was achieved over a scan area of 5 × 5 μm 2 with a polishing rate of ∼2.50 μm/hr. Further, this polished wafer was used as a template for the homoepitaxial re-growth of semi-polar (11–22) GaN epilayer. In comparison to as-grown and polished surfaces, the re-grown surface showed a good crystal quality with a reduced full width at half maximum (FWHM) value of 535 arc sec, obtained from X-ray Rocking Curve (XRC) along [11–2–3] direction. Around 0.3 GPa of in-plane stress relaxation has been observed for the re-grown epilayer in comparison to as-grown surface further indicating the improved structural quality. An improved rms surface roughness (∼58% over a scan area of 1.26 × 0.90 mm 2 ) has been achieved for the re-grown GaN epilayer (grown on the AFCMP treated atomically flat surface) as compared to the as-grown surface.